2021
DOI: 10.2340/jrm.v53.8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical therapy on impairments in COVID-19 patients from intensive care to home rehabilitation: A rapid review

Abstract: Objective: Guidelines regarding physical therapy for COVID-19 patients are often based on expert opinion. Recent clinical trials have reported effects on several rehabilitation outcomes in COVID-19 patients. This review summarizes the effects of physical therapy in COVID-19 patients. Data sources: PubMed, Web of Science and Scopus databases were systematically searched for studies investigating the effect of any physical therapy modality on impairments in adult COVID-19 patients. Included studies were (non)-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(139 reference statements)
0
7
0
1
Order By: Relevance
“…Previous reviews on rehabilitation interventions for patients with persisting symptoms after COVID-19 focussed on pulmonary rehabilitation [ 65 ] or only included RCTs [ 66 ]. Other reviews covered all or other (i.e., earlier) stages of rehabilitation of COVID-19 patients [ 67 69 ]. Their evidence suggests that, in line with our results, physical training and breathing exercises can be useful in patients with persisting symptoms after COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews on rehabilitation interventions for patients with persisting symptoms after COVID-19 focussed on pulmonary rehabilitation [ 65 ] or only included RCTs [ 66 ]. Other reviews covered all or other (i.e., earlier) stages of rehabilitation of COVID-19 patients [ 67 69 ]. Their evidence suggests that, in line with our results, physical training and breathing exercises can be useful in patients with persisting symptoms after COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation has been widely recommended in people with COVID-19 pneumonia [15]. In a meta-analysis examining the effect of physical therapy on COVID-19-related disorders, it was reported that physical therapy had positive effects on lung function, physical function, and psychosocial function [16]. Another study concluded that respiratory physiotherapy and physical rehabilitation practices in COVID-19 patients in ICU reduced ICU-related complications and increased patients' quality of life [17].…”
Section: Discussionmentioning
confidence: 99%
“…Asmenims, sirgusiems Covid-19, rekomenduojama reabilitacija, kurią sudaro raumenų jėgos bei pusiausvyros ir koordinacijos lavinimo, širdies ir kraujagyslių, kvėpavimo sistemų funkcinės būklės grąžinimo ir gerinimo pratimai (Wade, 2020;Agostini et al, 2021). Pasak Debeuf et al, (2022), veiksmingiausia reabilitacija yra ta, kurią sudaro kvėpavimo bei aerobinės ištvermės lavinimo pratimai. Reabilitaciją pasveikusiems nuo ligos rekomenduojama pradėti kuo anksčiau, nes tai skatina širdies ir kraujagyslių bei kvėpavimo sistemų funkcijų atsistatymą (Iannaccone et al, 2020).…”
Section: įVadasunclassified